1975
DOI: 10.1111/j.1432-1033.1975.tb02462.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pyruvate‐Dehydrogenase Complex from Azotobacter vinelandii

Abstract: Labelling studies with N-ethylmaleimide show that either in the presence of Mg2+, thiamine pyrophosphate (TPP) and pyruvate or in the presence of NADH the overall activity of the pyruvate dehydrogenase complex from Azotobuc'ter vinelundii is inhibited without much inhibition of the partial reactions. The complex undergoes a conformational change upon incubation with NADH. The inhibition by bromopyruvate is less specific.Specific incorporation of a fluorescent maleimide derivative was observed on the two transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
6
19
0
Order By: Relevance
“…Assuming four acetyl binding sites on both transacetylase chains, 3.9 -4.4 pyruvate dehydrogenase chains can be accomodated in the four-component complex. This value seems to be in good agreement with the number of Mn2+ binding sites reported earlier [19]. However, it is difficult to estimate accurately the actual number of binding sites from a non-linear Scatchard plot which shows at least three types of MnZ+ binding sites.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Assuming four acetyl binding sites on both transacetylase chains, 3.9 -4.4 pyruvate dehydrogenase chains can be accomodated in the four-component complex. This value seems to be in good agreement with the number of Mn2+ binding sites reported earlier [19]. However, it is difficult to estimate accurately the actual number of binding sites from a non-linear Scatchard plot which shows at least three types of MnZ+ binding sites.…”
Section: Discussionsupporting
confidence: 78%
“…The specificity of N-ethylmaleimide analogues for the lipoyl transacetylase component has been demonstrated by Grande et al [19,20] and Brown and Perham [21] and is confirmed in this report. The demonstration that nearly a 1 :1 ratio is obtained by using both labelled substrate and SH reagent confirms the '[able 5.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Prior to labelling the complex was treated with 1 mM N-ethylmaleimide as described previously [4]. Sodium dodecylsulphate gels without staining were used to determine the position of covalently bound fluorescent label.…”
Section: Methodsmentioning
confidence: 99%
“…there are two different transacetylase components in the A . vinelundii complex [4] and there is one such a component in the E. coli complex [3] as well as the much lower molecular weight and FAD content of the A . vinelundii complex.…”
mentioning
confidence: 99%